Assessing the working practices and the inclusive programs to students with disabilities in the Egyptian museums: challenges and possibilities for facilitating learning and promoting inclusion - Nevine Nizar Zakaria; Nevine Nizar Zakaria (Frontiers in Education, 2023)
Following the implementation of 2018’s laws on the rights of persons with disabilities (PWDs) in Egypt, students with disabilities (SWDs) have both legal and moral rights to meaningful learning opportunities and inclusive education. Despite that, SWDs still have very limited education resources which limit their career aspirations and quality of life. In this respect, education whether as part of formal education or lifelong learning is central to the museum’s mission. Museums, as part of non-formal education, are being acknowledged for their educative powers and investments in the development of quality formal, non-formal, and informal learning experiences. Further, phrases such as “inclusivity,” “accessibility,” and “diversity” were notably included in the newly approved museum definition by ICOM (2022) emphasizing museums’ obligations to embrace societal issues and shape a cultural attitude concerning disability rights, diversity, and equality together with overcoming exclusionary educational practices. The study seeks to investigate the existing resources and inclusive practices in Egyptian museums to achieve non-formal education for SWDs. Qualitative research approaches have been employed to answer a specific question: How can Egyptian museums work within their governing systems to support the learning of SWDs beyond their formal education system? The study aims to assess the potential of Egyptian museums in facilitating learning for SWDs. Further, it examines the capability of Egyptian museums in contributing to informal and non-formal learning for SWDs and striving for inclusive education inspired by the social model of disability that fosters inclusive educational programs and adopts a human rights-based approach. The results revealed that Egyptian museums contributed to the learning of SWDs, yet small-scale programs and individual efforts, but they are already engaged in active inclusive practices that address the learning of SWDs. The study suggests that they need to be acknowledged and supported by the government as state instruments and direct actors in advancing inclusive education and implementing appropriate pedagogies in favor of SWDs.